Personal Skills and Personality Development in Project Management Training: As they apply to Germany - Beatrix Palt (Adult Education Research Conference, 2014)
The discourse on the requirements for project managers is analyzed from the perspective of personality research and some implications for evolving a theory for developing project managers’ personality and for project management training are discussed.